SERVICE DELIVERY SYSTEM OF GOODS IN PT. ANDIARTA MUZIZAT (Courier & CARGO) USING MICROSOFT VISUAL BASIC VERSION 6.0 - Buchori Muslim (Jurnal Sistem Informasi, 2007)
Writing is about information delivery, because it is still a lack of computer tools, the part that handles shipping goods often have difficulty include: the length of the customer data record. Based on these circumstances, the author makes reference to the system by running the procedure, the system is expected to help overcome the problem that is useful to improve the efficiency, effectiveness and productivity and quality of service.